2012
DOI: 10.1245/s10434-011-2213-2
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma of Unknown Primary Origin

Abstract: Background Merkel cell carcinoma (MCC) is a rare neuroendocrine tumor of the skin. MCC from an unknown primary origin (MCCUP) can present a diagnostic and therapeutic challenge. We describe our single-institution experience with the diagnosis and management of MCCUP presenting as metastases to lymph nodes. Methods After institutional review board approval, our institutional database spanning the years 1998–2010 was queried for patients with MCCUP. Clinicopathologic variables and outcomes were assessed. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…One recent study revealed that the nodal Merkel cell carcinoma with an unknown extranodal primary had a lower recurrence rate and a less-aggressive clinical course, compared with the cutaneous Merkel cell carcinoma with nodal metastasis, with a median overall survival of B104 months in the nodal cases. 34 Another more recently published study showed that the overall 2-year survival of nodal Merkel cell carcinoma patients was significantly improved vs matched stage IIIB cutaneous Merkel cell carcinoma (76.9-36.4%). 35 …”
Section: Nodal Merkel Cell Carcinoma Shows Similar Clinical Featuresmentioning
confidence: 97%
“…One recent study revealed that the nodal Merkel cell carcinoma with an unknown extranodal primary had a lower recurrence rate and a less-aggressive clinical course, compared with the cutaneous Merkel cell carcinoma with nodal metastasis, with a median overall survival of B104 months in the nodal cases. 34 Another more recently published study showed that the overall 2-year survival of nodal Merkel cell carcinoma patients was significantly improved vs matched stage IIIB cutaneous Merkel cell carcinoma (76.9-36.4%). 35 …”
Section: Nodal Merkel Cell Carcinoma Shows Similar Clinical Featuresmentioning
confidence: 97%
“…A significant proportion of MCCUP patients (12.2%, 11/90) had a history of a previously or concurrent treated malignancy (eight basal cell carcinomas, one prostate cancer, three patients with chronic lymphocytic leukaemia), two patients were transplant recipients and another three patients were carriers of HIV. In the immunosupressed population an earlier median onset of the disease at 52 years (37-61) was observed [3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Almost all evaluable patients presented with clinically palpable non-tender lymph nodes-IIIB disease.…”
Section: Patients Characteristics and Clinical Presentationmentioning
confidence: 99%
“…Inguinal and axillary lymph node areas were initially involved in 40% (36/90) and 17.7% (16/90) of cases, respectively. Lesions ranged in colour from red, pink to blue of flesh-coloured, sometimes with a shiny surface which may mislead to a basal cell carcinoma diagnosis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Characteristics of all patients are summarised in Table 1 and are displayed in details in Table 2.…”
Section: Patients Characteristics and Clinical Presentationmentioning
confidence: 99%
“…Yet about 4%-14% of MCCs manifest as nodal or metastatic disease without a detectable primary tumor. [4][5][6] Pancreatic involvement by MCC is rare with 19 reported cases in the literature. [7][8][9][10][11][12][13][14][15][16][17][18][19] To date, only 8 cases have been diagnosed by endoscopic ultrasound-guided fine-needle aspiration cytology (EUS-FNA).…”
Section: Introductionmentioning
confidence: 99%